Pemberdayaan Masyarakat dalam Menurunkan Stunting sebagai Pencapaian Target SDGs di Desa Ulee Blang Mane Kota Lhokseumawe - Ardilla, Arista; Utaminingsih, Eka; Zulkarnaini, Zulkarnaini; Sari, Dian Vita (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background Stunting is one of the nation's problems that must be addressed immediately. According to the Ministry of Health's Basic Health Research (Riskesdas) data, the national stunting rate has decreased from 37.2% in 2013 to 30.8% in 2018. According to the Indonesian Toddler Nutrition Status Survey in 2019, this rate decreased to 27.7%. Stunting reduction has been declared a national priority program. This refers to the Sustainable Development Goals (SDGs) agenda which consists of 17 goals agreed upon by UN members, where the problem of stunting is one of the targets that must be considered. Purpose This activity aims to help improve the health status of the community, increase community knowledge, awareness and concern about stunting and increase community creativity in stunting prevention efforts through assistance in making nutritious food. Methods Face-to-face and counseling and conducting physical examinations of toddlers in Ulee Blang Manee Village. Results In Ulee Blang Mane Village there are 17 toddlers who are stunted. While the geographical conditions of Ulee Blang Mane village are still relatively close to the city center and also have the potential to grow the community's economy. This potential should be unique to the community in increasing family nutrition consumption so that it can reduce the problem of stunting. the results of the activity show that the Ulee Blang Mane village community has an increased understanding of how to prepare nutritious food to prevent stunting. Conclusion Appropriate and targeted socialization related to feeding toddlers is important to do and a more in-depth study is needed related to feeding by mothers or families including obstacles in its implementation.